Corporate governance : disclosure on directors’ remuneration in Malaysia – is it adequate? - Wong, Irene Ling Chiong (2014)
Ever since numerous corporate failures that shaken the faith and confidence of the public, the introduction of good corporate governance mechanism has swept the world off their feet. A sound corporate governance mechanism not only encourages proper management of risk, but at the same time, promotes effective performance. A vital part of corporate governance, directors’ remuneration has gain considerable focus from the policy makers, academics, media and public over the years. The measurements and determinants of the directors’ remuneration has attracts numerous different views and opinions which ultimately landed it as hot-debatable topic. The purpose of this study is to assess the adequacy of Malaysia’s current state on directors’ remuneration disclosure regime with the focus drawn upon six particular banking organisations since banking industry in Malaysia offers a diversified portfolio ranging from government-controlled, family-controlled to foreign-owned where effects of diversified ownership structures can be drawn. The paper outlines several angles: composition of remuneration and levels of remuneration and the process in determining the remuneration package i.e. remuneration committee. The benchmark is acquired by comparing Malaysia’s current disclosure regime with other countries’ regime. The paper concludes that Malaysia’s current disclosure regime is satisfactory but there are still some shortcomings and regulators need to overcome such inadequacies in order to achieve better corporate governance in the international arena.